Positive electrode material, preparation method thereof and sodium battery application
By using a structure of tunnel-type NaβMnO2 in the layered oxide core in the positive electrode material of sodium ion battery, the problem of poor cycle stability of existing positive electrode materials is solved, and better battery performance and life are achieved.
Patent Information
- Application Number
- CN202411726669.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-11-22
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
AI Technical Summary
The circulation stability of existing sodium ion battery positive electrode materials is poor, which limits the application of sodium ion battery.
The positive electrode material of tunnel-type NaβMnO2 is coated with the layered oxide core, and the material is prepared by wet ball milling or liquid phase coating.
The cycle stability and rate performance of the positive electrode material are improved, the internal structure changes are suppressed, and a stable protection interface is built, and the cycle life of the battery is extended.
Smart Images

Figure CN119542398A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a positive electrode material and a preparation method thereof and application in a sodium battery. Background Art
[0002] As an energy storage device, sodium-ion batteries have attracted much attention due to their advantages such as low cost, high efficiency, long life and high safety. The cathode material largely determines the overall performance and cost of the battery and is one of the main factors hindering the commercial application of sodium-ion batteries. The development of low-cost, long-life and high-performance cathode materials is of great significance for the practical application of sodium-ion batteries. Common cathode materials for sodium-ion batteries mainly include polyanionic compounds, Prussian blue analogs and transition metal oxides. The first two types of materials show good rate performance and cycle stability due to the stable three-dimensional skeleton and open three-dimensional channels in the main structure, but still have problems such as poor conductivity, difficult removal of crystal water and dissolution of transition metal ions. Layered transition metal oxides have become the preferred cathode materials for commercial applications of sodium-ion batteries due to their advantages such as high specific capacity, high energy density and simple synthesis process. However, the current conventional layered transition metal oxide cathode materials have poor cycle stability, which limits the application of sodium-ion batteries to a certain extent. Summary of the invention
[0003] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a positive electrode material, which is used in a sodium ion battery, and the battery has good cycle stability.
[0004] The invention also provides a method for preparing the positive electrode material.
[0005] The invention also provides a positive electrode.
[0006] The invention also provides a sodium battery.
[0007] The invention also provides an electrical device.
[0008] In a first aspect of the present invention, a positive electrode material is provided, comprising a layered oxide core and a shell coated on the surface of the core, wherein the core comprises Na α Fe x Mn y M z O 2 , the shell includes a tunnel-type Na β MnO 2 , wherein: M includes at least one of Li, Ni, Cu, Mg, Zn, Al or Ti, 0.66<α≤1, x+y+z=1, 0.30≤β≤0.66.
[0009] The positive electrode material according to the embodiment of the present invention has at least the following beneficial effects:
[0010] The present invention has a layered structure with a core and a tunnel-shaped structure. β MnO 2 , the outer layer of Na β MnO 2 Due to its tunnel structure, it is used in sodium batteries (such as sodium-ion batteries), allowing Na + Migrate in a jumping manner and highly reversible phase change during charge and discharge, resulting in good cycle stability and rate performance. At the same time, the two different structures of tunnel type and layered can produce an interfacial interlocking effect at the interface, effectively improving the structural stability of the positive electrode.
[0011] The outer shell has a tunnel structure and contains Na + , which can accelerate the diffusion rate of sodium ions. It can be used as a positive electrode material to supplement the sodium source to a certain extent, provide additional capacity for the electrode material, and effectively prevent the capacity loss caused by coating. β MnO 2 Due to its good water stability, the shell used as the coating core can improve the air stability of the core, and at the same time build a relatively stable interface layer on the surface of the positive electrode material to prevent direct contact between the electrode material and the electrolyte and inhibit the side reaction between them; Na β MnO 2 It can further relieve the structural stress accumulated in layered metal oxides due to repeated sodium insertion / deintercalation.
[0012] Therefore, the positive electrode material of the present invention is a layered structure with a tunnel-shaped Na β MnO 2 Using it in sodium batteries (such as sodium ion batteries) can not only effectively improve the air stability of the layered core, but also effectively inhibit internal structural changes, improve reaction kinetics, and build a stable protective interface on the surface, thereby increasing its cycle life and improving the battery's cycle stability.
[0013] In some embodiments of the invention, 0.70≤α≤1.
[0014] In some embodiments of the present invention, 0.03≤x≤0.80, such as optionally 0.05≤x≤0.60.
[0015] In some embodiments of the invention, 0.10≤x≤0.40.
[0016] In some embodiments of the present invention, 0.03≤y≤0.80, such as optionally 0.1≤y≤0.6.
[0017] In some embodiments of the invention, 0.2≤y≤0.5.
[0018] In some embodiments of the present invention, 0.06≤z≤0.85, such as optionally 0.2≤z≤0.7.
[0019] In some embodiments of the invention, 0.2≤z≤0.5.
[0020] In some embodiments of the present invention, the M includes Ni and at least one of Li, Cu, Mg, Zn, Al or Ti.
[0021] In some embodiments of the invention, the core comprises Na α Fe x Mn y Ni z O 2 Or Na α Fe x Mn y Ni z1 M' z2 O 2 At least one of the following, wherein M' is selected from at least one of Li, Cu, Mg, Zn, Al or Ti, and x+y+z1+z2=1. The core is a layered transition metal oxide.
[0022] In some embodiments of the present invention, 0.03≤z1≤0.40, such as 0.1≤z1≤0.3 can be selected.
[0023] In some embodiments of the present invention, 0.03≤z2≤0.45, such as optionally 0.1≤z2≤0.3.
[0024] In some embodiments of the invention, the core comprises NaFe 0.2~0.5 Mn 0.2~0.5 Ni 0.2~0.5 O 2 Or Na 0.70~1 Fe 0.1~0.3 Mn 0.2~0.5 Ni 0.1~0.3 M' 0.03~0.45 O 2 Optionally, the core comprises NaFe 0.2~0.4 Mn 0.2~0.4 Ni 0.2~0.4 O 2 Or Na 0.70~1 Fe 0.1~0.3 Mn 0.2~0.5 Ni 0.1~0.3 M' 0.03~0.45 O 2 At least one of .
[0025] In some embodiments of the invention, the core comprises Na 0.70 Li 0.05~ 0.15 Fe 0.1 Mn 0.4 Ni 0.2 Cu 0.05~0.15 Ti 0.05~0.15 O 2 .
[0026] In some embodiments of the present invention, 0.30≤β≤0.66, such as 0.30≤β≤0.44.
[0027] In some embodiments of the present invention, the shell is a tunnel-shaped Na 0.44 MnO 2 .
[0028] In some embodiments of the present invention, in the positive electrode material, the mass fraction of the shell is 0.5% to 10%, such as optionally 1% to 5%.
[0029] In some embodiments of the present invention, the average particle size of the positive electrode material is 0.5-5 μm, such as 1 μm.
[0030] In some embodiments of the present invention, the average thickness of the shell is 1 to 25 nm.
[0031] In a second aspect of the present invention, a method for preparing a positive electrode material is provided, comprising the following steps: preparing a shell on the surface of a core by a wet ball milling method or a liquid phase coating method to obtain the positive electrode material.
[0032] In some embodiments of the present invention, the wet ball milling method for preparing the shell comprises the following steps: mixing the inner core with a shell preparation raw material containing a sodium source and a manganese source, wet ball milling, and calcining to form the shell on the inner core surface.
[0033] In some embodiments of the present invention, the wet ball milling method for preparing the shell comprises the following steps: mixing the core, sodium source 1, manganese source 1 and liquid dispersant, ball milling, heating to remove the dispersant, calcining, and forming the shell on the surface of the core. Optionally, the core, sodium source 1 and manganese source 1 can be taken in a stoichiometric ratio according to the target shell composition and its proportion in the positive electrode material.
[0034] In some embodiments of the present invention, the dispersant includes but is not limited to acetone.
[0035] In some embodiments of the present invention, the sodium source includes at least one of sodium acetate, sodium hydroxide, sodium chloride, sodium sulfate, sodium nitrate, sodium bicarbonate or sodium carbonate.
[0036] In some embodiments of the present invention, the manganese source includes at least one of manganese acetate, manganese chloride, manganese sulfate, manganese nitrate or manganese carbonate.
[0037] In some embodiments of the present invention, in the step of wet ball milling, the rotation speed of the ball mill is 100 to 700 rpm, and optionally, the rotation speed of the ball mill is 300 to 500 rpm.
[0038] In some embodiments of the present invention, in the step of wet ball milling, the ball milling time is 1 to 15 hours, and optionally, the ball milling time can be 4 to 12 hours.
[0039] In some embodiments of the present invention, in the step of wet ball milling, the heating temperature is 30-100°C, such as 60-90°C, and further 70-90°C.
[0040] In some embodiments of the present invention, in the step of wet ball milling, the calcination temperature is 700-1100°C, such as 800-1000°C, and further 800-900°C.
[0041] In some embodiments of the present invention, in the step of wet ball milling, the calcination time is 8 to 20 hours, such as 10 to 15 hours.
[0042] In some embodiments of the present invention, in the wet ball milling step, the mass ratio of the dispersant to the core is (1-10):1, such as (2-6):1, and further 4:1.
[0043] In some embodiments of the present invention, the liquid phase coating method for preparing the shell comprises the following steps: mixing the core, the solvent, and the shell preparation raw materials containing the complexing agent, the sodium source II, and the manganese source II, removing the solvent, calcining, and forming the shell on the surface of the core. Optionally, the core, the sodium source II, and the manganese source II can be taken according to the stoichiometric ratio according to the target shell composition and its proportion in the positive electrode material.
[0044] Through the above implementation, the shell is prepared by the liquid phase coating method, so that the complexing agent can better adsorb metal ions and allow them to adhere closely to the surface of the core, and then through high temperature calcination, a coating shell that is more suitable for the core is formed, and the coating effect is good. The positive electrode material is used in sodium ion batteries, and the battery performance is better.
[0045] In some embodiments of the present invention, in the step of the liquid phase coating method, the calcination temperature is 800-1000°C.
[0046] In some embodiments of the present invention, in the step of the liquid phase coating method, the calcination time is 8 to 20 hours, such as optionally 10 to 15 hours.
[0047] In some embodiments of the present invention, in the step of the liquid phase coating method, the ratio of the amount of the core to the solvent is 1g:(30-300)mL, such as 1g:(50-150)mL, and further 1g:(60-100)mL.
[0048] In some embodiments of the present invention, the complexing agent includes at least one of polyvinyl pyrrolidone (PVP), polyethylene glycol, carboxymethyl cellulose or oxalic acid.
[0049] In some embodiments of the present invention, the mass ratio of the complexing agent, the sodium source II and the manganese source II is (7-20):1:(4-10), such as (8-16):1:(5-9), and further 15:1:7.
[0050] In some embodiments of the present invention, the sodium source 2 and the sodium source 1 may be the same or different. Optionally, the sodium source 2 comprises at least one of sodium acetate, sodium hydroxide, sodium chloride, sodium sulfate, sodium nitrate, sodium bicarbonate or sodium carbonate.
[0051] In some embodiments of the present invention, the second manganese source and the first manganese source may be the same or different. Optionally, the second manganese source includes at least one of manganese acetate, manganese chloride, manganese sulfate, manganese nitrate or manganese carbonate.
[0052] In some embodiments of the present invention, the solvent comprises at least one of water, methanol, ethanol, propanol or acetone. In some embodiments of the present invention, the solvent is water and ethanol. Optionally, the volume ratio of water to ethanol is 1:(5-20), such as 1:(7-12).
[0053] In some embodiments of the present invention, the liquid phase coating method for preparing the shell comprises the following steps:
[0054] S1, mixing a mixture A containing a core and a solvent with a mixture B containing a complexing agent and a solvent to obtain a mixture C;
[0055] S2, mixing the mixture C with a mixture D containing a sodium source II, a manganese source II, and a solvent to obtain a mixture E;
[0056] S3, heating the mixture E to remove the solvent, and calcining to obtain the positive electrode material.
[0057] In some embodiments of the present invention, step S1 further includes: mixing the core and part of the solvent to obtain a mixture A; and mixing the complexing agent and part of the solvent to obtain a mixture B.
[0058] In some embodiments of the present invention, in step S3, the heating temperature is 30-100°C.
[0059] In some embodiments of the present invention, the liquid phase coating method further comprises mixing a second sodium source, a second manganese source, and the remaining solvent to obtain the mixture D.
[0060] In some embodiments of the present invention, in the mixture A, the ratio of the amount of the core to the amount of the solvent is 1 g: (50-150) mL.
[0061] In some embodiments of the present invention, when preparing mixture B, the ratio of the amount of complexing agent to the amount of solvent is 1 g: (50-200) mL.
[0062] In some embodiments of the present invention, in the mixture D, the sum of the masses of the sodium source II and the manganese source II is a, the volume of the solvent is b, and a:b=1 g:(10-300) mL.
[0063] In some embodiments of the present invention, the preparation method further includes preparing an inner core, specifically including the following steps: taking a sodium source three, an iron source, a manganese source three and an M source, ball milling, calcining, and obtaining the inner core. Optionally, the sodium source three includes at least one of sodium hydroxide, hydrochloride, sulfate, nitrate, bicarbonate or carbonate; the iron source includes at least one of iron oxide, hydroxide, hydrochloride, sulfate, nitrate, bicarbonate or carbonate; the manganese source three includes at least one of manganese oxide, hydroxide, hydrochloride, sulfate, nitrate, bicarbonate or carbonate; the M source includes at least one of M oxide, hydroxide, hydrochloride, sulfate, nitrate, bicarbonate or carbonate. The sodium source three, iron source, manganese source three and M source can be taken according to the composition of the target inner core in a stoichiometric ratio.
[0064] In some embodiments of the present invention, the sodium source comprises Na 2 CO 3 or at least one of NaOH.
[0065] In some embodiments of the present invention, the iron source includes but is not limited to Fe 2 O 3 One or more of iron oxides, hydroxides, hydrochlorides, sulfates, nitrates, bicarbonates or carbonates.
[0066] In some embodiments of the present invention, the manganese source includes but is not limited to Mn 2 O 3 One or more of manganese oxides, hydroxides, hydrochlorides, sulfates, nitrates, bicarbonates or carbonates.
[0067] In some embodiments of the present invention, the M source comprises at least one of a nickel source or an M' source. Alternatively, the M' source comprises at least one of an oxide, hydroxide, hydrochloride, sulfate, nitrate, bicarbonate or carbonate of M'.
[0068] In some embodiments of the present invention, the nickel source includes but is not limited to one or more of nickel oxides, hydroxides, hydrochlorides, sulfates, nitrates, bicarbonates or carbonates such as NiO.
[0069] In some embodiments of the present invention, the M' source includes at least one of a titanium source, a lithium source, a copper source, a magnesium source, a zinc source or an aluminum source.
[0070] In some embodiments of the present invention, the titanium source includes but is not limited to TiO 2 One or more of titanium oxides, hydroxides, hydrochlorides, sulfates, nitrates, bicarbonates or carbonates.
[0071] In some embodiments of the present invention, the lithium source includes but is not limited to Li 2 One or more of the oxides, hydroxides, hydrochlorides, sulfates, nitrates, bicarbonates or carbonates of lithium such as CO.
[0072] In some embodiments of the present invention, the copper source includes, but is not limited to, one or more of copper oxides, hydroxides, hydrochlorides, sulfates, nitrates, bicarbonates or carbonates such as CuO.
[0073] In some embodiments of the present invention, the magnesium source includes, but is not limited to, one or more of magnesium oxides such as magnesium oxide, hydroxides, hydrochlorides, sulfates, nitrates, bicarbonates or carbonates.
[0074] In some embodiments of the present invention, the zinc source includes, but is not limited to, one or more of zinc oxides such as zinc oxide, hydroxides, hydrochlorides, sulfates, nitrates, bicarbonates or carbonates.
[0075] In some embodiments of the present invention, the aluminum source includes, but is not limited to, one or more of aluminum oxides such as aluminum oxide, hydroxides, hydrochlorides, sulfates, nitrates, bicarbonates or carbonates.
[0076] In some embodiments of the present invention, in the step of preparing the inner core, the rotation speed of the ball mill is 100 to 700 rpm, and the ball milling time is 1 to 20 hours. Optionally, the ball milling time is 1 to 6 hours.
[0077] In some embodiments of the present invention, in the step of preparing the inner core, the calcination temperature is 600-1000°C, such as 650-950°C.
[0078] In some preferred embodiments of the present invention, in the step of preparing the inner core, the calcination temperature is 660-790°C, such as 680-780°C.
[0079] Through the above implementation, it is easier to first generate a P-phase structure at a core preparation calcination temperature of 660 to 790°C, with a larger interlayer spacing. When the shell material is coated and calcined at a high temperature, sodium ions are more likely to migrate to form a more stable interface layer, so the resulting battery has better performance.
[0080] In some embodiments of the present invention, in the step of preparing the inner core, the calcination time is 5 to 20 hours, such as 10 to 15 hours.
[0081] In the present invention, the calcination step of the shell is combined with a method for preparing a positive electrode material by two-step sintering. In the process of preparing the core, the low-temperature pre-sintering first generates a P phase structure. When the high-temperature sintering of the shell preparation step is performed, the Na atoms in the P phase core structure move to form an O phase. At the same time, the Na atoms and Mn atoms of the sodium salt and manganese salt on the surface also move synchronously, making the interface interlocking tighter, so that the O phase of the core and the tunnel phase of the outer layer are formed at the same time, and the interface lattice is more matched. β MnO 2 (If it can be Na 0.44 MnO 2 ) has better structural stability and can be well fixed to the surface even if the core phase lattice expands and contracts during the charge and discharge process, thereby improving the cycle life of the coated sample.
[0082] In addition, the raw materials used in the process of synthesizing the positive electrode material in the present invention are abundant in reserves, low in cost and environmentally friendly. The strategy for synthesizing the core and shell is simple and effective, and a layered transition metal oxide@tunnel-type transition metal oxide composite positive electrode material with uniform composition and relatively uniform coating thickness can be obtained. This method is easy to scale up from laboratory preparation to industrial production, and has good industrial prospects. Moreover, the layered core in the positive electrode material is coated with a unique three-dimensional "S"-shaped tunnel structure of Na β MnO 2 Using it in sodium batteries (such as sodium ion batteries) can not only effectively improve the air stability of the layered core, but also effectively inhibit internal structural changes, improve reaction kinetics, and build a stable protective interface on the surface, thereby increasing its cycle life and improving the battery's cycle stability.
[0083] According to a third aspect of the present invention, a positive electrode is provided, comprising the positive electrode material mentioned above.
[0084] In a fourth aspect of the present invention, a sodium battery is provided, comprising the above-mentioned positive electrode or the above-mentioned positive electrode material.
[0085] In some embodiments of the invention, the sodium battery comprises a sodium ion battery.
[0086] According to a fifth aspect of the present invention, an electrical device is provided, comprising the above-mentioned sodium battery, wherein the sodium battery is used as a power source for the electrical device. BRIEF DESCRIPTION OF THE DRAWINGS
[0087] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:
[0088] Figure 1 This is a schematic diagram of the process of preparing positive electrode materials according to Example 11 of the present invention;
[0089] Figure 2 The microstructure test results of the positive electrode material of Example 1 of the present invention are as follows: Figure 1 ;
[0090] Figure 3 The microstructure test results of the positive electrode material of Example 1 of the present invention are as follows: Figure 2 ;
[0091] Figure 4 The positive electrode material of Example 1 of the present invention is used to prepare a battery at 2-4V 20mA g -1 Constant current charge and discharge curve diagram;
[0092] Figure 5 The positive electrode material of Example 11 of the present invention is used to prepare a battery at 2-4V 100mA g -1 Performance test result chart of 250 cycles;
[0093] Figure 6 XRD diagram of the positive electrode material of Example 11 of the present invention after being placed in air at RH=60% for 0h, 24h and 72h;
[0094] Figure 7 These are the XRD diagrams of the positive electrode material of Comparative Example 2 of the present invention after being placed in air at RH=60% for 0 h and 72 h. DETAILED DESCRIPTION
[0095] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0096] The experimental methods in the following examples without specifying specific conditions are generally carried out according to conventional conditions in the art or conditions recommended by the manufacturers; the raw materials and reagents used, unless otherwise specified, are all raw materials and reagents that can be obtained from commercial channels such as conventional markets.
[0097] Example 1
[0098] This embodiment discloses a positive electrode material, and its preparation process specifically includes:
[0099] (1) Preparation of the core: Na 2 CO 3 、NiO、Mn 2 O 3 , Fe 2 O 3 The powder, with a ball-to-material ratio of 5:1, was ball-milled at 400 rpm for 10 h, calcined at 900 °C in an air atmosphere in a muffle furnace for 12 h, and cooled naturally to obtain NaFe 1 / 3 Mn 1 / 3 Ni 1 / 3 O 2 Kernel powder.
[0100] (2) Preparation of the shell, comprising: dissolving 0.582 g of the core powder obtained in step (1) in 30 mL of anhydrous ethanol and stirring evenly, named solution A; dissolving 0.1 g of a complexing agent polyvinyl pyrrolidone (PVP) in 10 mL of anhydrous ethanol and stirring evenly (e.g. stirring for half an hour), named solution B; and slowly adding solution B to solution A at a rate of 1 mL / min and stirring at 500 rpm for 30 min to obtain complex C. 3 COONa and Mn(CH 3 COO 2 ·4H 2 O was dispersed in 10 mL of anhydrous ethanol and stirred evenly, named solution D. Then solution D was slowly added to solution C at a rate of 1 mL / min, and the anhydrous ethanol was removed by heating and stirring at 80 °C. Then, Na was calcined in a muffle furnace at 800 °C in air atmosphere for 12 h to obtain Na 0.44 MnO 2 Coated NaFe 1 / 3 Mn 1 / 3 Ni 1 / 3 O 2 Cathode material, abbreviated as: NaFe 1 / 3 Mn 1 / 3 Ni 1 / 3 O 2 @Na 0.44 MnO 2 , among which the mass proportion of the shell in the positive electrode material is 3%.
[0101] This embodiment discloses a positive electrode sheet, including the positive electrode material prepared in this embodiment. The positive electrode sheet is prepared by a method including the following steps:
[0102] The positive electrode material, Super P and polyvinylidene fluoride (PVDF) were mixed in a weight ratio of 8:1:1, and 1-methyl 2-pyrrolidone (NMP) was used as the solvent. After ball milling at different speeds in a planetary mixer for 15 minutes, the electrode slurry was prepared. The obtained slurry was coated on a carbon-coated aluminum foil (Cruder, MA-EN-CU-000303) and dried in a vacuum oven at 100°C for 10 hours. The average mass of the electrode load is about 1-2 mg cm -2 .
[0103] This embodiment discloses a sodium ion battery, including the positive electrode of this embodiment or the positive electrode material prepared in this embodiment.
[0104] This embodiment also discloses an electrical device, including the sodium ion battery of this embodiment, and the sodium ion battery is used as a power source for the electrical device.
[0105] Example 2
[0106] This embodiment discloses a positive electrode material, which is different from the embodiment 1 in that step (2) is different. Step (2) of this embodiment includes:
[0107] 3.950 g of core powder and stoichiometric Na 2 CO 3 、MnCO 3 After mixing, 20 mL of acetone was added as a dispersant, and the ball-to-material ratio was 5:1. After ball milling at 350 rpm for 4 h, the acetone was removed by heating at 80 °C with continued stirring, and then calcined at 800 °C in an air atmosphere in a muffle furnace for 12 h to obtain Na 0.44 MnO 2 Coated NaFe 1 / 3 Mn 1 / 3 Ni 1 / 3 O 2 The positive electrode material is abbreviated as: NaFe 1 / 3 Mn 1 / 3 Ni 1 / 3 O 2 @Na 0.44 MnO 2 The mass proportion of the shell in the positive electrode material is 3%.
[0108] This embodiment also discloses a positive electrode sheet, including the positive electrode material prepared in this embodiment. The difference between the preparation method of the positive electrode sheet in this embodiment and that in embodiment 1 is that the positive electrode material prepared in this embodiment is used to replace the positive electrode material in embodiment 1, and the rest is the same as in embodiment 1.
[0109] This embodiment also discloses a sodium ion battery, including the positive electrode of this embodiment or the positive electrode material prepared in this embodiment.
[0110] This embodiment also discloses an electrical device, including the sodium ion battery of this embodiment, and the sodium ion battery is used as a power source for the electrical device.
[0111] Example 3
[0112] This embodiment discloses a positive electrode material, which differs from the embodiment 1 in that: in step (2), NaFe 1 / 3 Mn 1 / 3 Ni 1 / 3 O 2 Core powder and CH 3 COONa and Mn(CH 3 COO 2 ·4H 2 O mass ratio, and Na 0.44 MnO 2 Coated NaFe 1 / 3 Mn 1 / 3 Ni 1 / 3 O 2 The positive electrode material is abbreviated as: NaFe 1 / 3 Mn 1 / 3 Ni 1 / 3 O 2 @Na 0.44 MnO 2 The mass proportion of the shell in the positive electrode material is 1%.
[0113] This embodiment also discloses a positive electrode sheet, including the positive electrode material prepared in this embodiment. The difference between the preparation method of the positive electrode sheet in this embodiment and that in embodiment 1 is that the positive electrode material prepared in this embodiment is used to replace the positive electrode material in embodiment 1, and the rest is the same as in embodiment 1.
[0114] This embodiment also discloses a sodium ion battery, including the positive electrode of this embodiment or the positive electrode material prepared in this embodiment.
[0115] This embodiment also discloses an electrical device, including the sodium ion battery of this embodiment, and the sodium ion battery is used as a power source for the electrical device.
[0116] Example 4
[0117] This embodiment discloses a positive electrode material, which is different from the embodiment 1 in that: NaFe is changed 1 / 3 Mn 1 / 3 Ni 1 / 3 O 2 Core powder and CH 3 COONa and Mn(CH 3 COO 2 ·4H 2 O mass ratio, and Na 0.44 MnO 2 Coated NaFe 1 / 3 Mn 1 / 3 Ni 1 / 3 O 2 The positive electrode material is abbreviated as: NaFe 1 / 3 Mn 1 / 3 Ni 1 / 3 O 2 @Na 0.44 MnO 2 The mass proportion of the shell in the positive electrode material is 5%.
[0118] This embodiment also discloses a positive electrode sheet, including the positive electrode material prepared in this embodiment. The difference between the preparation method of the positive electrode sheet in this embodiment and that in embodiment 1 is that the positive electrode material prepared in this embodiment is used to replace the positive electrode material in embodiment 1, and the rest is the same as in embodiment 1.
[0119] This embodiment also discloses a sodium ion battery, including the positive electrode of this embodiment or the positive electrode material prepared in this embodiment.
[0120] This embodiment also discloses an electrical device, including the sodium ion battery of this embodiment, and the sodium ion battery is used as a power source for the electrical device.
[0121] Example 5
[0122] This embodiment discloses a positive electrode material, which is different from Embodiment 1 in that the complexing agent used in step (2) of this embodiment is oxalic acid, which is different from PVP in Embodiment 1.
[0123] This embodiment also discloses a positive electrode sheet, including the positive electrode material prepared in this embodiment. The difference between the preparation method of the positive electrode sheet in this embodiment and that in embodiment 1 is that the positive electrode material prepared in this embodiment is used to replace the positive electrode material in embodiment 1, and the rest is the same as in embodiment 1.
[0124] This embodiment also discloses a sodium ion battery, including the positive electrode of this embodiment or the positive electrode material prepared in this embodiment.
[0125] This embodiment also discloses an electrical device, including the sodium ion battery of this embodiment, and the sodium ion battery is used as a power source for the electrical device.
[0126] Example 6
[0127] This embodiment discloses a positive electrode material, which is different from the embodiment 1 in that: the complexing agent used in step (2) of this embodiment is polyethylene glycol (weight average molecular weight is 300), which is different from PVP in embodiment 1; at the same time, the step of preparing solution B is: dissolving 0.1g polyethylene glycol in 10mL mixed solvent, wherein the mixed solvent is a mixed solution of deionized water and anhydrous ethanol in a volume ratio of 1:9, to obtain solution B. The remaining steps are the same as in embodiment 1.
[0128] This embodiment also discloses a positive electrode sheet, including the positive electrode material prepared in this embodiment. The difference between the preparation method of the positive electrode sheet in this embodiment and that in embodiment 1 is that the positive electrode material prepared in this embodiment is used to replace the positive electrode material in embodiment 1, and the rest is the same as in embodiment 1.
[0129] This embodiment also discloses a sodium ion battery, including the positive electrode of this embodiment or the positive electrode material prepared in this embodiment.
[0130] This embodiment also discloses an electrical device, including the sodium ion battery of this embodiment, and the sodium ion battery is used as a power source for the electrical device.
[0131] Example 7
[0132] This embodiment discloses a positive electrode material, which is different from the embodiment 1 in that: the complexing agent used in step (2) of this embodiment is carboxymethyl cellulose CMC2200, which is different from PVP in the embodiment 1; meanwhile, the step of preparing solution B is: dissolving 0.1 g of carboxymethyl cellulose CMC2200 in 10 mL of a mixed solvent, wherein the mixed solvent is a mixture of deionized water and anhydrous ethanol in a volume ratio of 1:9, to obtain solution B. The remaining steps are the same as those in the embodiment 1.
[0133] This embodiment also discloses a positive electrode sheet, including the positive electrode material prepared in this embodiment. The difference between the preparation method of the positive electrode sheet in this embodiment and that in embodiment 1 is that the positive electrode material prepared in this embodiment is used to replace the positive electrode material in embodiment 1, and the rest is the same as in embodiment 1.
[0134] This embodiment also discloses a sodium ion battery, including the positive electrode of this embodiment or the positive electrode material prepared in this embodiment.
[0135] This embodiment also discloses an electrical device, including the sodium ion battery of this embodiment, and the sodium ion battery is used as a power source for the electrical device.
[0136] Example 8
[0137] This embodiment discloses a positive electrode material, and its preparation process specifically includes (the flow chart is as follows Figure 1 shown):
[0138] (1) Preparation of the core: Na 2 CO 3 、NiO、Mn 2 O 3 , Fe 2 O 3 , Li 2 CO 3 、TiO 2 The CuO powder was ball-milled at 400 rpm with a ball-to-material ratio of 5:1 for 10 h, then calcined at 950 °C in an air atmosphere in a muffle furnace for 12 h and cooled naturally to obtain Na 0.70 Li 0.1 Fe 0.1 Mn 0.4 Ni 0.2 Cu 0.1 Ti 0.1 O 2 Kernel powder.
[0139] (2) Preparation of the shell, comprising: dissolving 0.582 g of the core powder obtained in step (1) in 30 mL of anhydrous ethanol and stirring evenly, named solution A; dissolving 0.1 g of oxalic acid in 10 mL of anhydrous ethanol and stirring evenly, named solution B; and slowly adding solution B to solution A and stirring for 30 min to obtain complex C. 3 COONa and Mn(CH 3 COO 2 ·4H 2 O was dispersed in 10 mL of anhydrous ethanol and stirred evenly, named solution D, and then solution D was added dropwise to solution C, and the anhydrous ethanol was removed by heating and stirring at 80 °C, and then calcined in a muffle furnace at 950 °C in air atmosphere for 12 h to obtain Na 0.44 MnO 2 Coating Na 0.70 Li 0.1 Fe 0.1 Mn 0.4 Ni 0.2 Cu 0.1 Ti 0.1 O 2 The positive electrode material is abbreviated as: Na 0.70 Li 0.1 Fe 0.1 Mn 0.4 Ni 0.2 Cu 0.1 Ti 0.1 O2 @Na 0.44 MnO 2 The mass proportion of the shell in the positive electrode material is 3%.
[0140] This embodiment also discloses a positive electrode sheet, including the positive electrode material prepared in this embodiment. The difference between the preparation method of the positive electrode sheet in this embodiment and that in embodiment 1 is that the positive electrode material prepared in this embodiment is used to replace the positive electrode material in embodiment 1, and the rest is the same as in embodiment 1.
[0141] This embodiment also discloses a sodium ion battery, including the positive electrode of this embodiment or the positive electrode material prepared in this embodiment.
[0142] This embodiment also discloses an electrical device, including the sodium ion battery of this embodiment, and the sodium ion battery is used as a power source for the electrical device.
[0143] Example 9
[0144] This embodiment discloses a positive electrode material, which is different from the embodiment 8 in that step (1) is different. Step (1) of this embodiment is: Na 2 CO 3 、NiO、Mn 2 O 3 , Fe 2 O 3 , Li 2 CO 3 、TiO 2 The CuO powder was ball-milled at 400 rpm with a ball-to-material ratio of 5:1 for 10 h, then calcined at 650 °C in an air atmosphere in a muffle furnace for 12 h and cooled naturally to obtain Na 0.70 Li 0.1 Fe 0.1 Mn 0.4 Ni 0.2 Cu 0.1 Ti 0.1 O 2 (P phase) core powder.
[0145] This embodiment also discloses a positive electrode sheet, including the positive electrode material prepared in this embodiment. The difference between the preparation method of the positive electrode sheet in this embodiment and that in embodiment 1 is that the positive electrode material prepared in this embodiment is used to replace the positive electrode material in embodiment 1, and the rest is the same as in embodiment 1.
[0146] This embodiment also discloses a sodium ion battery, including the positive electrode of this embodiment or the positive electrode material prepared in this embodiment.
[0147] This embodiment also discloses an electrical device, including the sodium ion battery of this embodiment, and the sodium ion battery is used as a power source for the electrical device.
[0148] Example 10
[0149] This embodiment discloses a positive electrode material, which differs from Embodiment 9 in that the calcination temperature of step (1) is different. In step (1) of this embodiment, the calcination step is calcined at 700° C. for 12 h, and the rest is the same as Embodiment 9.
[0150] This embodiment also discloses a positive electrode sheet, including the positive electrode material prepared in this embodiment. The difference between the preparation method of the positive electrode sheet in this embodiment and that in embodiment 1 is that the positive electrode material prepared in this embodiment is used to replace the positive electrode material in embodiment 1, and the rest is the same as in embodiment 1.
[0151] This embodiment also discloses a sodium ion battery, including the positive electrode of this embodiment or the positive electrode material prepared in this embodiment.
[0152] This embodiment also discloses an electrical device, including the sodium ion battery of this embodiment, and the sodium ion battery is used as a power source for the electrical device.
[0153] Embodiment 11
[0154] This embodiment discloses a positive electrode material, which differs from Embodiment 9 in that the calcination temperature of step (1) is different. In step (1) of this embodiment, the calcination step is calcined at 750° C. for 12 h, and the rest is the same as Embodiment 9.
[0155] This embodiment also discloses a positive electrode sheet, including the positive electrode material prepared in this embodiment. The difference between the preparation method of the positive electrode sheet in this embodiment and that in embodiment 1 is that the positive electrode material prepared in this embodiment is used to replace the positive electrode material in embodiment 1, and the rest is the same as in embodiment 1. In this embodiment, the prepared positive electrode material (RH=60% air placed for 0h) is directly used to prepare the positive electrode sheet.
[0156] This embodiment also discloses a sodium ion battery, including the positive electrode of this embodiment or the positive electrode material prepared in this embodiment.
[0157] This embodiment also discloses an electrical device, including the sodium ion battery of this embodiment, and the sodium ion battery is used as a power source for the electrical device.
[0158] Example 12
[0159] This embodiment discloses a positive electrode material, which differs from Embodiment 9 in that the calcination temperature of step (1) is different. In step (1) of this embodiment, the calcination step is calcined at 800° C. for 12 h, and the rest is the same as Embodiment 9.
[0160] This embodiment also discloses a positive electrode sheet, including the positive electrode material prepared in this embodiment. The difference between the preparation method of the positive electrode sheet in this embodiment and that in embodiment 1 is that the positive electrode material prepared in this embodiment is used to replace the positive electrode material in embodiment 1, and the rest is the same as in embodiment 1.
[0161] This embodiment also discloses a sodium ion battery, including the positive electrode of this embodiment or the positive electrode material prepared in this embodiment.
[0162] This embodiment also discloses an electrical device, including the sodium ion battery of this embodiment, and the sodium ion battery is used as a power source for the electrical device.
[0163] Embodiment 13
[0164] This embodiment discloses a positive electrode sheet, which is different from Embodiment 11 only in that the prepared positive electrode material is placed in air at RH=60% for 24 hours before preparing the positive electrode sheet.
[0165] This embodiment also discloses a sodium ion battery, including the positive electrode of this embodiment or the positive electrode material prepared in this embodiment.
[0166] This embodiment also discloses an electrical device, including the sodium ion battery of this embodiment, and the sodium ion battery is used as a power source for the electrical device.
[0167] Embodiment 14
[0168] This embodiment discloses a positive electrode sheet, which is different from Embodiment 11 in that the prepared positive electrode material is placed in air at RH=60% for 72 hours before preparing the positive electrode sheet.
[0169] This embodiment also discloses a sodium ion battery, including the positive electrode of this embodiment or the positive electrode material prepared in this embodiment.
[0170] This embodiment also discloses an electrical device, including the sodium ion battery of this embodiment, and the sodium ion battery is used as a power source for the electrical device.
[0171] The average particle size of the positive electrode material prepared in each embodiment is 0.5-5 μm, and the average thickness of the coating shell is 1-25 nm.
[0172] Comparative Example 1
[0173] This comparative example discloses a positive electrode material, and its preparation process specifically comprises: 2 CO 3 、NiO、Mn 2 O 3 , Fe 2 O 3The powder was ball-milled at 400 rpm with a ball-to-material ratio of 5:1 for 10 h, then calcined at 900 °C in an air atmosphere in a muffle furnace for 12 h and cooled naturally to obtain NaFe 1 / 3 Mn 1 / 3 Ni 1 / 3 O 2 Positive electrode powder.
[0174] This comparative example discloses a positive electrode sheet. The difference between the preparation method of the positive electrode sheet of this comparative example and that of Example 1 is that the positive electrode material prepared in this comparative example is used instead of the positive electrode material of Example 1, and the rest is the same as Example 1.
[0175] Comparative Example 2
[0176] This comparative example discloses a positive electrode material, and its preparation process specifically comprises: 2 CO 3 、NiO、Mn 2 O 3 , Fe 2 O 3 , Li 2 CO 3 、TiO 2 The CuO powder was ball-milled at 400 rpm with a ball-to-material ratio of 5:1 for 10 h, calcined at 950 °C in an air atmosphere in a muffle furnace for 12 h, and cooled naturally to obtain Na 0.70 Li 0.1 Fe 0.1 Mn 0.4 Ni 0.2 Cu 0.1 Ti 0.1 O 2 powder.
[0177] This comparative example discloses a positive electrode sheet. The difference between the preparation method of the positive electrode sheet of this comparative example and that of Example 1 is that the positive electrode material prepared in this comparative example is used instead of the positive electrode material of Example 1, and the rest is the same as Example 1.
[0178] Test example
[0179] This test example performs performance tests on the positive electrode materials and batteries of each embodiment and comparative example, specifically including:
[0180] 1) The microstructure of the product prepared in Example 1 was tested, and the test results are as follows: Figure 2 , Figure 3 As shown ( Figure 3 The coating layer shown in is the outer shell of the positive electrode material).
[0181] 2) The positive electrode sheets of each embodiment and comparative example are used to make batteries and perform battery performance tests, including:
[0182] The prepared positive electrode sheet and metallic sodium (thickness about 1 mm) were assembled into a CR2032 button battery in a glove box filled with Ar. The separator was Whatman GF / D glass fiber, and the electrolyte was 1 mol / L NaClO 4 The solution has a solvent of EC (ethylene carbonate) / diethyl carbonate (DEC) (v:v=1:1) and contains 5 vol% of a fluoroethylene carbonate (FEC) additive, which helps to improve the stability of the solid electrolyte interface film.
[0183] The obtained battery was subjected to constant current charge and discharge tests on the LAND CT3002A battery test system, with a current density of 100 mA g -1 The test results of the batteries made of the positive electrode materials of Comparative Example 1 and Examples 1 to 7 are shown in Table 1; the test results of the batteries made of the positive electrode materials of Comparative Examples 1 to 2 and Examples 1, 8 to 14 are shown in Table 2.
[0184] also, Figure 4 The positive electrode material of Example 1 is used to prepare a battery at 2-4V 20mA g -1 Constant current charge and discharge curve diagram.
[0185] Table 1
[0186]
[0187] In Examples 6 and 7, polyethylene glycol and carboxymethyl cellulose are not soluble in anhydrous ethanol, and a deionized water / ethanol (v:v=1:9) mixed solution is used in the preparation of the outer shell coating layer. Compared with Examples 6 and 7, the solvent used in the complexing agent of Examples 1 and 5 does not contain deionized water, and is less likely to destroy the structure of the core material or cause sodium loss during the synthesis process, so the performance of the resulting battery is better.
[0188] Figure 5 Example 11 of the present invention prepares a positive electrode material for a battery at 2-4V 100mA g -1 Performance test result diagram after 250 cycles; the P-phase core and tunnel structure shell formed in this embodiment have better interface compatibility, facilitate sodium ion migration, and achieve a better solution for electrochemical performance.
[0189] Table 2
[0190]
[0191] Among them, compared with Examples 8-9 and 12, the core preparation calcination temperature of Examples 10-11 is easier to form a P phase structure at a more preferred temperature (660-790°C), the interlayer spacing is larger, and when the shell material is coated and calcined at high temperature, the sodium ions are more likely to migrate and form a more stable interface layer, so the resulting battery performance is better. In addition, the capacity retention rate of Examples 8-12 is higher than that of Example 1, the reason is that: multi-element doping reduces the content of active elements Ni, Fe, and Mn, although it causes a decrease in capacity, but doping plays a role in stabilizing the structure, so the cycle performance is significantly improved.
[0192] 3) Figure 6 The XRD diagram of the positive electrode material of Example 11 of the present invention after being placed in air at RH=60% for 0h, 24h, and 72h, Figure 7 The XRD graphs of the positive electrode material of Example 2 placed in air at RH=60% for 0h and 72h are shown. By comparing the XRD graphs of the materials before and after coating placed in air at RH=60% for 72h, it can be found that the characteristic peak intensity of the material before coating becomes weaker or even disappears after the air aging test, indicating that it is corroded by air. However, the characteristic peak of the coated material has almost no change after the air aging test. The above results show that the positive electrode material of the present invention has excellent air stability.
[0193] As can be seen from the above, the positive electrode material of the embodiment of the present invention has excellent cycle stability and air stability. As in Embodiment 1-2 of the present invention, compared with the wet ball milling method (Example 2), the positive electrode material (Example 1) is prepared by the liquid phase coating method to obtain the shell, and the coating effect is better, and the stability of the positive electrode material is improved to a higher degree: wherein, through the liquid phase coating, the complexing agent can better adsorb metal ions and allow them to adhere closely to the surface of the core, and then through high temperature calcination, a coating shell that is more compatible with the core is formed.
[0194] The positive electrode material shell Na 0.44 MnO 2 The unique three-dimensional "S"-shaped tunnel structure can accelerate the diffusion rate of sodium ions, and it can be used as a positive electrode material to supplement the sodium source to a certain extent. The positive electrode material of the present invention can not only effectively improve the air stability of the layered material, but also effectively inhibit the internal structural changes, improve the reaction kinetics, and build a stable protective interface on the surface to improve its cycle life.
[0195] Optionally, firstly α Fe x Mn y M z O 2The first sintering treatment is performed at different temperatures, such as 600°C, 650°C, 700°C, 750°C, and 800°C to generate a P phase structure, and then sintering at Na α Fe x Mn y M z O 2 (P phase) is treated with liquid phase coating by different complexing agents, and the coated material is then sintered at high temperature to obtain Na β MnO 2 Coating Na α Fe x Mn y M z O 2 The composite cathode material is a layered / tunnel-type composite structure transition metal oxide cathode material. The tunnel-type Na β MnO 2 As a shell coating Na α Fe x Mn y M z O 2 The core modification strategy is used to improve the air stability of layered oxides, thereby enhancing the rate performance and cycle stability of layered oxide materials.
[0196] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A positive electrode material, characterized in that: It includes a layered oxide core and a shell coated on the surface of the core, wherein the core includes Na α Fe x Mn y M z O2, the shell includes a tunnel-type Na β MnO2, wherein: M includes at least one of Li, Ni, Cu, Mg, Zn, Al or Ti, 0.66<α≤1, x+y+z=1, 0.30≤β≤0.
66.
2. The positive electrode material according to claim 1, characterized in that 0.03≤x≤0.80; or / and, 0.03≤y≤0.80; or / and, 0.06≤z≤0.85; or / and, the shell is a tunnel-type Na 0.44 MnO2; or / and, in the positive electrode material, the mass fraction of the shell is 0.5% to 10%; or / and, the M includes Ni and at least one of Li, Cu, Mg, Zn, Al or Ti; or / and, the average particle size of the positive electrode material is 0.5 to 5 μm; or / and, the average thickness of the shell is 1 to 25 nm.
3. The positive electrode material according to claim 1, characterized in that The core includes Na α Fe x Mn y Ni z O2 or Na α Fe x Mn y Ni z1 M' z2 O2, wherein M' is selected from at least one of Li, Cu, Mg, Zn, Al or Ti, and x+y+z1+z2=1; Preferably, 0.03≤z1≤0.40; and / or, 0.03≤z2≤0.45; Preferably, the core comprises NaFe 0.2~0.5 Mn 0.2~0.5 Ni 0.2~0.5 O2 or Na 0.70~1 Fe 0.1~0.3 Mn 0.2~0.5 Ni 0.1~ 0.3 M' 0.03~0.45 At least one of O2.
4. A method for preparing the positive electrode material according to claim 1, characterized in that: The method comprises the following steps: preparing a shell on the surface of a core by a wet ball milling method or a liquid phase coating method to obtain the positive electrode material.
5. The method for preparing the positive electrode material according to claim 4, characterized in that: The wet ball milling method for preparing the shell comprises the following steps: mixing the inner core with the shell preparation raw material containing a sodium source 1 and a manganese source 1, wet ball milling, calcining, and forming the shell on the surface of the inner core; Preferably, the wet ball milling method for preparing the shell comprises the following steps: mixing the inner core, a sodium source 1, a manganese source 1 and a liquid dispersant, ball milling, heating to remove the dispersant, calcining, and forming the shell on the surface of the inner core. Preferably, the dispersant comprises acetone; or / and, the sodium source comprises at least one of sodium acetate, sodium hydroxide, sodium chloride, sodium sulfate, sodium nitrate, sodium bicarbonate or sodium carbonate; or / and, the manganese source comprises at least one of manganese acetate, manganese chloride, manganese sulfate, manganese nitrate or manganese carbonate; or / and, the ball milling speed is 100-700 rpm, and the ball milling time is 1-15 h; or / and, the calcination temperature is 700-1100° C.; or / and, the calcination time is 8-20 h.
6. The method for preparing the positive electrode material according to claim 4, characterized in that: The liquid phase coating method for preparing the shell comprises the following steps: mixing the core, the solvent and the shell preparation raw materials containing the complexing agent, the sodium source II and the manganese source II, removing the solvent, calcining, and forming the shell on the surface of the core; Preferably, the calcination temperature is 800-1000° C.; or / and, the calcination time is 8-20 h; or / and, the complexing agent includes at least one of polyvinyl pyrrolidone, polyethylene glycol, carboxymethyl cellulose or oxalic acid; or / and, the second sodium source includes at least one of sodium acetate, sodium hydroxide, sodium chloride, sodium sulfate, sodium nitrate, sodium bicarbonate or sodium carbonate; or / and, the second manganese source includes at least one of manganese acetate, manganese chloride, manganese sulfate, manganese nitrate or manganese carbonate; or / and, the solvent includes at least one of water, methanol, ethanol, propanol or acetone; Preferably, the liquid phase coating method for preparing the shell comprises the following steps: S1, mixing a mixture A containing a core and a solvent with a mixture B containing a complexing agent and a solvent to obtain a mixture C; S2, mixing the mixture C with a mixture D containing a sodium source II, a manganese source II, and a solvent to obtain a mixture E; S3, heating the mixture E to remove the solvent, and calcining to obtain the positive electrode material.
7. The method for preparing the positive electrode material according to claim 4, characterized in that: The preparation method also includes preparing the inner core, which specifically includes the following steps: taking a sodium source three, an iron source, a manganese source three and an M source, ball milling, and calcining to obtain the inner core; Preferably, the sodium source three includes at least one of sodium hydroxide, hydrochloride, sulfate, nitrate, bicarbonate or carbonate; the iron source includes at least one of iron oxide, hydroxide, hydrochloride, sulfate, nitrate, bicarbonate or carbonate; the manganese source three includes at least one of manganese oxide, hydroxide, hydrochloride, sulfate, nitrate, bicarbonate or carbonate; the M source includes at least one of M oxide, hydroxide, hydrochloride, sulfate, nitrate, bicarbonate or carbonate; Preferably, the rotation speed of the ball mill is 100-700 rpm, and the ball milling time is 1-20 h; or / and, the calcination temperature is 600-1000° C.; or / and, the calcination time is 5-20 h.
8. A positive electrode, characterized in that The positive electrode material comprises the positive electrode material described in any one of claims 1 to 3 or the positive electrode material prepared by the method described in any one of claims 4 to 7.
9. A sodium battery, characterized in that: A positive electrode material comprising any one of claims 1 to 3 or a positive electrode material prepared by the method of any one of claims 4 to 7 or a positive electrode according to claim 8; Preferably, the sodium battery comprises a sodium ion battery.
10. An electrical device, characterized in that: The sodium battery according to claim 9 is used as a power source for the electrical equipment.
Citation Information
Cited By
Method for preparing fast-charging long-life sodium electrooxide positive electrode based on in-situ epitaxial growth
CN120157195A